Prediction of Rainfall Intensity as Early Warning Information on Potential Landslides using Fuzzy Logic (Case Study West Lampung Regency) - Daniel Rinaldi; Rahman Indra Kesuma; M. Yafi Fahmi; Winda Yulita; Mugi Praseptiawan; Aidil Afriansyah (IJISTECH (International Journal of Information System and Technology), 2021)
Landslides always happened in West Lampung Regency yearly, which makes early warning information of landslides is needed. There are many factors which can cause landslide, one of the important factors is rainfall intensity, which can be predicted. The prediction of rainfall intensity can be obtained by using fuzzy logic. The fuzzy logic used in this research is Mamdani, and this research show the similar result for most data which means that fuzzy logic might not be suitable to be used to forecast the rainfall if the obtained data has lots of missing values.